Titanium sulfate modified vanadium-based denitration catalyst and preparation method thereof

CN122912882APending Publication Date: 2026-10-16SHANGHAI INST OF CERAMIC CHEM & TECH CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510417086.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-03
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]针对上述钒基催化剂中低温脱硝活性下降、抗碱金属中毒性能弱以及现有硫酸化工艺中操作繁琐、效果有限的问题,本发明的目的在于提供一种硫酸氧钛改性的钒基脱硝催化剂及其制备方法

Benefits of technology

(1)本发明提供的硫酸氧钛改性的钒基脱硝催化剂,在500ppm NH3、500ppm NO、3%O2,N2作为平衡气,总流量100mL/min,相应空速(GHSV)为120000mL/(h*gcat)的气氛中,SCR脱硝效率在150~250℃低温区间内与不含硫酸氧钛的普通钒基催化剂相比提高11~15%,在300~400℃高温区间内脱硝效率高于95%;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912882A_ABST
    Figure CN122912882A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of titanium sulfate modified vanadium-based denitration catalyst and its preparation method.The titanium sulfate modified vanadium-based denitration catalyst includes: carrier, and active component and adjuvant loaded on the carrier;Wherein, the carrier includes anatase titanium dioxide containing titanium sulfate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of flue gas denitrification catalyst materials, specifically relating to a vanadium-based denitrification catalyst modified with titanium oxysulfate and its preparation method. Background Technology

[0002] Nitrogen oxides (NO) x NOx is a significant air pollutant produced by the combustion of fossil fuels, easily causing acid rain, photochemical smog, and ozone layer depletion, and is also physiologically toxic to plants, animals, and humans. Selective catalytic reduction (NH3-SCR) is currently the most widely used industrial method for NOx removal. x In flue gas denitrification technology, the catalyst is the core of NH3-SCR technology. Among various systems, V2O5-WO3 / TiO2 catalysts are widely used in the treatment of exhaust gases from stationary sources such as thermal power, steel, and waste incineration, as well as mobile sources such as automobiles and ships, due to their low cost, simple preparation process, and high denitrification activity and stability in the high-temperature range of 300-400℃. However, when the operating temperature drops to 150-250℃, the denitrification activity of ordinary vanadium-based catalysts will decrease significantly; moreover, when the flue gas contains a large amount of alkali metals, ordinary vanadium-based catalysts are easily affected and poisoned, leading to catalyst deactivation and reduced service life. Therefore, how to improve the low-temperature denitrification performance of vanadium-based catalysts, broaden the temperature window, and enhance their resistance to alkali metal poisoning is an important issue in the field of flue gas denitrification applications.

[0003] As is well known, acidity and redox properties are important factors affecting the denitrification activity of vanadium-based catalysts. Current academic research and industrial applications have found that acidification treatment of vanadium-based catalysts is an effective means to improve the denitrification activity at medium and low temperatures and the resistance to alkali metal poisoning. One of the common acidification treatment methods is sulfation, which can be further divided into: (1) before the operation of the flue gas denitrification system, gaseous sulfur dioxide is introduced to treat the catalyst for a period of time; (2) during catalyst preparation, the titanium dioxide support is pretreated with sulfuric acid. Both of these methods form a Bronsted acidic Ti-OS structure on the surface of the support, which can provide additional acidic sites for the catalyst, adsorb NH3 and other reactant molecules in the NH3-SCR reaction, and preferentially bind with toxic substances such as alkali metal particles in the flue gas, thus improving the low-temperature denitrification activity and the resistance to alkali metal poisoning.

[0004] However, both processes are complex to implement and have significant room for simplification. Furthermore, method (2) reduces the redox properties of the catalyst, negatively impacting its denitrification activity. Summary of the Invention

[0005] To address the problems of decreased low-temperature denitration activity, weak resistance to alkali metal poisoning, and cumbersome operation and limited effectiveness in existing sulfation processes, the present invention aims to provide a vanadium-based denitration catalyst modified with titanium oxysulfate and its preparation method. This catalyst has a simple preparation method, exhibits significantly improved catalytic denitration activity in the medium-low temperature range of 150–250°C, and possesses excellent resistance to alkali metal poisoning, making it suitable for industrial applications.

[0006] In a first aspect, the present invention provides a vanadium-based denitration catalyst modified with titanium oxysulfate, the titanium oxysulfate-modified vanadium-based denitration catalyst comprising: a support, and an active component and an additive supported on the support; wherein the support comprises anatase titanium dioxide containing titanium oxysulfate.

[0007] Preferably, the mass fraction of the titanium oxysulfate in the support is ≥5 wt% and <30 wt%, more preferably 5 to 25 wt%, and most preferably 10 to 20 wt%.

[0008] Preferably, the active component includes vanadium pentoxide, and the auxiliary component includes tungsten oxide or molybdenum oxide.

[0009] Preferably, based on 100 wt% of the total mass of the vanadium-based denitration catalyst modified with titanium oxysulfate, the carrier mass percentage is 88-97.5 wt%, preferably 90-96 wt%; the active component mass percentage can be 0.5-5.0 wt%, preferably 0.6-3.0 wt%; and the additive mass percentage can be 2.0-10.0 wt%, preferably 3.0-8.0 wt%.

[0010] Secondly, the present invention provides a method for preparing the above-mentioned titanium oxysulfate modified vanadium-based denitration catalyst, the preparation method comprising the following steps: adding a solution containing ammonium metavanadate and ammonium metatungstate / ammonium heptamolybdate to a mixed support material of titanium sulfate and titanium dioxide, mixing evenly, and then drying and calcining to obtain the titanium oxysulfate modified vanadium-based denitration catalyst.

[0011] Preferably, the mass ratio of titanium sulfate to titanium dioxide is 2 to 10:25.

[0012] Preferably, the molar ratio of ammonium metavanadate to co-solvent is 1:2 to 3, more preferably 1:2; the mass ratio of titanium sulfate, ammonium metavanadate, and ammonium metatungstate / ammonium heptamolybdate is 100 to 800: 9 to 90: 30 to 250.

[0013] Preferably, the calcination heating rate is 2-10℃ / min, more preferably 2℃ / min; the calcination temperature is 300-650℃, more preferably 300-500℃; and the calcination time is 3-6h, more preferably 4h.

[0014] Beneficial effects (1) The vanadium-based denitration catalyst modified with titanium oxysulfate provided in this invention, with 500 ppm NH3, 500 ppm NO, 3% O2, and N2 as the balance gas, and a total flow rate of 100 mL / min, has a corresponding space velocity (GHSV) of 120000 mL / (h*g). cat In an atmosphere of ), the SCR denitrification efficiency is 11-15% higher than that of ordinary vanadium-based catalysts without titanium oxysulfate in the low temperature range of 150-250℃, and the denitrification efficiency is higher than 95% in the high temperature range of 300-400℃. (2) The vanadium-based denitration catalyst modified with titanium oxysulfate provided by this invention, with 500 ppm NH3, 500 ppm NO, 3% O2, and N2 as the balance gas, a total flow rate of 100 mL / min, and a corresponding space velocity (GHSV) of 50000 mL / (h*g) cat In an atmosphere of ), the SCR denitrification efficiency is 8-29% higher than that of ordinary vanadium-based catalysts without oxysulfate in the low-temperature range of 150-300℃; and the denitrification efficiency is higher than 95% in the high-temperature range of 250-450℃, which is 100℃ wider than that of ordinary vanadium-based catalysts. (3) The vanadium-based denitrification catalyst modified with titanium oxysulfate provided by the present invention, under a 1wt% K2O loading and at the same space velocity as above, has an SCR denitrification efficiency that is 4-19% higher than that of ordinary vanadium-based catalyst without titanium oxysulfate in the whole temperature range of 150-400℃. That is, it has a significantly higher resistance to alkali metal poisoning and the highest denitrification efficiency can reach more than 90%. (4) The vanadium-based denitration catalyst modified with titanium oxysulfate of the present invention has a simple preparation process, obvious modification effect and low cost compared with the traditional sulfation modification method, and is particularly suitable for industrial production. Attached Figure Description

[0015] Figure 1 The diagram shows the denitrification efficiency of the catalysts prepared in Examples 1-3 and Comparative Example 1 at different temperatures under high mass space velocity. Figure 2 The figure shows the denitrification efficiency of the catalysts prepared in Comparative Examples 1 and 2 of this invention at different temperatures under high mass space velocity. Figure 3 The diagram shows the denitrification efficiency of the catalysts prepared in Example 2 and Comparative Example 1 of the present invention at different temperatures and at lower mass hourly space velocities. Figure 4 The denitrification efficiency of the catalysts prepared in Example 2 and Comparative Example 1 of this invention and their K2O-supported catalysts at high mass space velocity is shown in the graph. Figure 5 The NH3-TPD curves of the catalysts prepared in Examples 1-3 and Comparative Example 1 of this invention are shown. Figure 6 The H2-TPR curves are for the catalysts prepared in Examples 1-3 and Comparative Example 1 of this invention. Detailed Implementation

[0016] The present invention will be further illustrated by the following embodiments. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the present invention.

[0017] Given that the sulfation process in current vanadium-based catalyst research typically requires cumbersome steps, this invention provides a vanadium-based denitration catalyst modified with titanium oxysulfate. The titanium oxysulfate-modified vanadium-based denitration catalyst may include: a support, and active components and additives supported on the support.

[0018] In some embodiments, the carrier may include anatase titanium dioxide containing titanium oxysulfate; preferably, the mass fraction of titanium oxysulfate in the carrier may be ≥5 wt% and <30 wt%, more preferably 5 to 25 wt%, and most preferably 10 to 20 wt%, and the mass fraction of anatase titanium dioxide in the carrier may be 70 to 95 wt%.

[0019] This invention sulfatates the catalyst by mixing a titanium sulfate precursor into a conventional titanium dioxide support and generating titanium oxysulfate in situ during subsequent calcination. This eliminates the need for cumbersome procedures such as liquid acid impregnation, pH adjustment, and aging with dry acidic gas, as well as the addition of additional chelating agents or other reagents. The process is convenient and cost-effective. In the catalyst prepared by this method, a Ti-OS structure is formed between the sulfate ion and the support, providing additional bronsted acidity that serves as an additional adsorption site for the reactant gas NH3, promoting rapid NH3-SCR via the Eley-Rideal reaction pathway. Titanium oxysulfate also enhances the catalyst's redox properties, promoting the participation of vanadium species and surface-active oxygen in the redox cycle, thereby improving catalytic activity. Furthermore, the additional acidic sites preferentially bind to alkali metals, protecting vanadium species from poisoning and achieving an anti-alkali metal poisoning effect.

[0020] In some embodiments, the active component may include vanadium pentoxide, and the auxiliary component may include tungsten oxide or molybdenum oxide.

[0021] In some embodiments, based on a total mass of 100 wt% of the titanium oxysulfate modified vanadium-based denitration catalyst, the mass percentage of the support can be 88–97.5 wt%, preferably 90–96 wt%; the mass percentage of the active component can be 0.5–5.0 wt%, preferably 0.6–3.0 wt%; and the mass percentage of the additive can be 2.0–10.0 wt%, preferably 3.0–8.0 wt%. If the mass percentages of the active component and the additive are lower than the above ranges, the catalytic performance of the material will decrease; if they are higher than the above ranges, the active component will crystallize or sinter, resulting in differences in the physicochemical properties of the catalyst.

[0022] In some embodiments, the vanadium-based denitration catalyst modified with titanium oxysulfate is used with 400-600 ppm NH3, 400-1000 ppm NO, 3-10% O2, and N2 as the balance gas, at a total flow rate of 100 mL / min, and a catalyst dosage of 50-1000 mg, resulting in a corresponding space velocity (GHSV) of 30000-150000 mL / (h*g). cat In an atmosphere of ), the SCR denitrification efficiency is 5-30% higher than that of ordinary vanadium-based catalysts without titanium oxysulfate in the low-temperature range of 150-300℃, and the denitrification efficiency is higher than 95% in the high-temperature range of 250-450℃.

[0023] In some embodiments, the titanium oxysulfate modified vanadium-based denitration catalyst is supported on 0.5–2.0 wt% K₂O, with a corresponding space velocity (GHSV) of 30,000–150,000 mL / (h*g). cat Under the conditions of ), the SCR denitrification efficiency is 4-20% higher than that of ordinary vanadium-based catalysts without oxysulfate titanium in the entire temperature range of 150-400℃, which means that it has a significantly higher resistance to alkali metal poisoning and the highest denitrification efficiency can reach more than 90%.

[0024] The following is an exemplary description of a method for preparing the vanadium-based denitration catalyst modified with titanium oxysulfate according to the present invention. The preparation method may include the following steps: (1) Place the titanium sulfate precursor and titanium dioxide in an agate mortar and grind them evenly to obtain the carrier material; (2) Dissolve ammonium metavanadate, ammonium metatungstate / ammonium heptamolybdate and cosolvent in water and stir until homogeneous to obtain a mixed solution; (3) Add the mixed solution obtained in step (2) to the carrier material obtained in step (1), mix evenly, and then treat with ultrasound to impregnate the carrier. (4) The uniform material system impregnated with the carrier in step (3) is left to stand at room temperature for 5 to 12 hours, then transferred to an oven to dry, and finally placed in a muffle furnace for calcination to obtain the vanadium-based denitrification catalyst modified with titanium oxysulfate.

[0025] In some embodiments, in step (1), the mass ratio of the titanium sulfate precursor to titanium dioxide can be 2 to 10:25.

[0026] In some embodiments, in step (2), the co-solvent can be anhydrous oxalic acid; the molar ratio of ammonium metavanadate to the co-solvent can be 1:2 to 3, preferably 1:2; the mass ratio of titanium sulfate (precursor), ammonium metavanadate, and ammonium metatungstate / ammonium heptamolybdate can be 100 to 800: 9 to 90: 30 to 250; preferably, the stirring temperature can be 40 to 60°C, preferably 60°C; the stirring time can be 5 to 20 min, preferably 15 min.

[0027] In some embodiments, in step (3), the mixing time and ultrasonic treatment time can be 5 to 30 minutes, preferably 15 minutes.

[0028] In some embodiments, in step (4), the drying temperature can be 80-100°C and the drying time can be 3-5 hours.

[0029] In some embodiments, in step (4), the calcination heating rate can be 2-10℃ / min, preferably 2℃ / min; the calcination temperature is 300-650℃, preferably 300-500℃; and the calcination time is 3-6h, preferably 4h. If the calcination heating rate, holding temperature, and time are not properly controlled, the titanium sulfate precursor will undergo excessive decomposition, resulting in a large loss of sulfate ions and affecting the acidity of the catalyst.

[0030] The vanadium-based denitrification catalyst modified with titanium oxysulfate prepared by the method provided in this invention can be used for NH3-SCR flue gas denitrification in applications such as petrochemical industry, thermal power generation industry, and waste incineration industry.

[0031] As an example, the NH3-SCR flue gas denitrification may include the following steps: pressing, crushing, sieving, and placing the vanadium-based denitrification catalyst modified with titanium oxysulfate into tablets in a fixed-bed reactor; flue gas enters from one side of the denitrification device, passes through a catalyst layer, and is discharged from the bottom of the device to complete the denitrification reaction.

[0032] In some embodiments, the catalyst is in the form of fine particles or powder, with a particle size of 20 to 80 mesh.

[0033] The following examples further illustrate the present invention in detail. It should also be understood that the following examples are only for further explanation of the present invention and should not be construed as limiting the scope of protection of the present invention. Any non-essential improvements and adjustments made by those skilled in the art based on the above description of the present invention are within the scope of protection of the present invention. The specific process parameters, etc., in the following examples are merely examples within a suitable range; that is, those skilled in the art can make appropriate selections within the range based on the description herein, and are not intended to be limited to the specific values ​​in the examples below. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art.

[0034] Example 1

[0035] The preparation method of the vanadium-based denitration catalyst modified with titanium oxysulfate provided in this embodiment includes the following steps: (1) Accurately weigh 1.6674g Ti(SO4)2 and 10g anatase TiO2 and place them in an agate mortar. Grind them thoroughly for 15 minutes to obtain the carrier material. (2) Accurately measure 10 mL of deionized water into a beaker using a graduated cylinder, then accurately weigh 0.1503 g (0.00128 mol) of ammonium metavanadate, 0.2314 g (0.00257 mol) of anhydrous oxalic acid, and 0.3858 g of ammonium metatungstate, and add them in order to the aforementioned beaker containing deionized water. Stir in a 60°C water bath for 5 min to obtain a mixed solution. (3) Carefully pour the above mixed solution into the carrier material obtained in step (1), stir with a glass rod for 15 minutes, and transfer it to an ultrasonic machine for 15 minutes to impregnate the carrier. (4) The uniform material system impregnated with the carrier in step (3) was left to stand at room temperature for 12 hours, and then transferred to an oven at 100°C to dry for 5 hours. After drying, the obtained solid was transferred to a ceramic crucible and ground into fine powder. It was then heated to 500°C in a muffle furnace at a heating rate of 2°C / min and calcined for 4 hours to obtain the vanadium-based denitration catalyst modified with titanium oxysulfate (denoted as 1V3W-T10, in which titanium oxysulfate accounts for 10wt% of the carrier).

[0036] Example 2

[0037] The preparation method of the vanadium-based denitration catalyst modified with titanium oxysulfate provided in this embodiment includes the following steps: (1) Accurately weigh 2.6482g Ti(SO4)2 and 10g anatase TiO2 and place them in an agate mortar. Grind them thoroughly for 15 minutes to obtain the carrier material. (2) Accurately measure 10 mL of deionized water into a beaker using a graduated cylinder, then accurately weigh 0.1592 g (0.00136 mol) of ammonium metavanadate, 0.2450 g (0.00272) of anhydrous oxalic acid, and 0.4085 g of ammonium metatungstate, and add them in order to the aforementioned beaker containing deionized water. Stir in a 60°C water bath for 5 min to obtain a mixed solution. (3) Carefully pour the above mixed solution into the carrier material obtained in step (1), stir with a glass rod for 15 minutes, and transfer it to an ultrasonic machine for 15 minutes to impregnate the carrier. (4) The uniform material system impregnated with the carrier in step (3) was left to stand at room temperature for 12 hours, and then transferred to an oven at 100°C to dry for 5 hours. After drying, the obtained solid was transferred to a ceramic crucible and ground into fine powder. It was then heated to 500°C in a muffle furnace at a heating rate of 2°C / min and calcined for 4 hours to obtain the vanadium-based denitration catalyst modified with titanium oxysulfate (denoted as 1V3W-T15, in which titanium oxysulfate occupies 15wt% of the carrier).

[0038] Further, 2 mL of deionized water was accurately measured using a graduated cylinder, and 0.0376 g of KNO3 was accurately weighed and dissolved in the water. The solution was stirred at room temperature for 10 min to obtain a KNO3 solution. 2 g of the above 1V3W-T15 catalyst was dispersed in the KNO3 solution and stirred for 10 min. The solution was then transferred to an ultrasonic machine for 10 min. The above material system was filtered using a water-circulating vacuum pump and a Buchner funnel and washed with deionized water. The resulting filter cake was dried at 80 °C for 12 h and then transferred to a ceramic crucible. It was then calcined in a muffle furnace at a heating rate of 2 °C / min to 450 °C for 3 h to obtain the composite material 1K-1V3W-T15 loaded with 1 wt% K2O.

[0039] Example 3

[0040] The preparation method of the vanadium-based denitration catalyst modified with titanium oxysulfate provided in this embodiment includes the following steps: (1) Accurately weigh 1.8758g Ti(SO4)2 and 5g anatase TiO2 and place them in an agate mortar. Grind them thoroughly for 15 minutes to obtain the carrier material. (2) Accurately measure 5 mL of deionized water into a beaker using a graduated cylinder, then accurately weigh 0.0846 g (0.00072 mol) ammonium metavanadate, 0.1301 g (0.00144 mol) anhydrous oxalic acid, and 0.2170 g ammonium metatungstate, and add them in order to the aforementioned beaker containing deionized water. Stir in a 60°C water bath for 5 min to obtain a mixed solution. (3) Carefully pour the above liquid into the carrier material obtained in step (1), stir with a glass rod for 15 minutes, and transfer it to an ultrasonic machine for 15 minutes to impregnate the carrier. (4) The uniform material system impregnated with the carrier described in step (3) was left to stand at room temperature for 12 hours, and then transferred to an oven at 100°C to dry for 5 hours. After drying, the obtained solid was transferred to a ceramic crucible and ground into fine powder. It was then heated to 500°C in a muffle furnace at a heating rate of 2°C / min and calcined for 4 hours to obtain the vanadium-based denitration catalyst modified with titanium oxysulfate (1V3W-T20, in which titanium oxysulfate accounts for 20wt% of the carrier).

[0041] Comparative Example 1

[0042] The preparation method of the vanadium-based denitration catalyst provided in this comparative example includes the following steps: (1) Accurately weigh 10g of anatase TiO2 for later use; (2) Accurately measure 10 mL of deionized water into a beaker using a graduated cylinder, then accurately weigh 0.1353 g of ammonium metavanadate, 0.2082 g of anhydrous oxalic acid, and 0.3472 g of ammonium metatungstate, and add them in order to the aforementioned beaker containing deionized water. Stir in a 60°C water bath for 5 min to obtain a mixed solution. (3) Carefully pour the above mixed solution into TiO2 in step (1), stir with a glass rod for 15 min, and transfer it to an ultrasonic machine for 15 min for carrier impregnation. (4) The material system impregnated with the carrier in step (3) was left to stand at room temperature for 12 hours, and then transferred to an oven at 100°C to dry for 5 hours. After drying, the obtained solid was transferred to a ceramic crucible and ground into fine powder. It was then heated to 500°C in a muffle furnace at a heating rate of 2°C / min and calcined for 4 hours to obtain the vanadium-based denitration catalyst (denoted as 1V3W-T0, the catalyst does not contain titanium oxysulfate).

[0043] Further, 2 mL of deionized water was accurately measured using a graduated cylinder, and 0.0376 g of KNO3 was accurately weighed and dissolved in the water. The solution was stirred at room temperature for 10 min to obtain a KNO3 solution. 2 g of the above 1V3W-T0 catalyst was dispersed in the KNO3 solution and stirred for 10 min. The solution was then transferred to an ultrasonic machine for 10 min. The above material was filtered using a water-circulating vacuum pump and a Buchner funnel and washed with deionized water. The resulting filter cake was dried at 80 °C for 12 h and then transferred to a ceramic crucible. It was then calcined in a muffle furnace at a heating rate of 2 °C / min to 450 °C for 3 h to obtain the composite material 1K-1V3W-T0 loaded with 1 wt% K2O.

[0044] Comparative Example 2

[0045] The preparation method of the vanadium-based denitration catalyst provided in this comparative example includes the following steps: (1) Accurately weigh 3.2156g Ti(SO4)2 and 5g anatase TiO2 and place them in an agate mortar. Grind them thoroughly for 15 minutes to obtain the carrier material. (2) Accurately measure 5 mL of deionized water into a beaker using a graduated cylinder, then accurately weigh 0.0966 g (0.00082 mol) of ammonium metavanadate, 0.1487 g (0.00165 mol) of anhydrous oxalic acid, and 0.2480 g of ammonium metatungstate, and add them in order to the aforementioned beaker containing deionized water. Stir in a 60°C water bath for 5 min to obtain a mixed solution. (3) Carefully pour the above liquid into the carrier material obtained in step (1), stir with a glass rod for 15 minutes, and transfer it to an ultrasonic machine for 15 minutes to impregnate the carrier. (4) The uniform material system impregnated with the carrier in step (3) was left to stand at room temperature for 12 hours, and then transferred to an oven at 100°C to dry for 5 hours. After drying, the obtained solid was transferred to a ceramic crucible and ground into fine powder. It was then heated to 500°C in a muffle furnace at a heating rate of 2°C / min and calcined for 4 hours to obtain the vanadium-based denitration catalyst modified with titanium oxysulfate (1V3W-T30, in which titanium oxysulfate accounts for 30 wt% of the carrier).

[0046] The catalyst materials prepared in the above embodiments and comparative examples were then tested. The specific conversion rates, etc., in the following test examples are merely example values ​​within a suitable range; that is, those skilled in the art can select appropriate values ​​within the range based on the description herein, and are not intended to be limited to the specific values ​​shown in the examples below.

[0047] Test Example 1

[0048] The denitrification performance of catalysts 1V3W-T10, 1V3W-T15, 1V3W-T20, and 1V3W-T0 prepared in Examples 1-3 and Comparative Example 1 was tested in a fixed-bed reactor. The catalytic reaction conditions were: NH3: 500 ppm, NO: 500 ppm, O2: 3%, N2 as the balance gas, total gas flow rate 100 mL / min, catalyst dosage 0.0500 g, and space velocity GHSV = 120000 mL / (h*g). cat The NO content in the exhaust gas was determined using gas chromatography-mass spectrometry (GC-MS) at a reaction temperature of 150-400℃.

[0049] Figure 1The graphs show the denitrification efficiency of the catalysts prepared in Examples 1-3 and Comparative Example 1 at different temperatures under high mass hourly space velocities. As can be seen from the graphs, when the test temperature is 150-250℃, the denitrification efficiency of the catalysts in the examples is significantly higher than that in Comparative Example 1, with the catalyst in Example 2 showing the best denitrification performance, increasing the denitrification efficiency by 11-15%. When the test temperature is 300-400℃, the denitrification efficiency of the catalysts in the examples can all remain above 95%.

[0050] Test Example 2

[0051] The denitrification performance of catalysts 1V3W-T0 and 1V3W-T30 prepared in Comparative Examples 1 and 2 was tested in a fixed-bed reactor. The catalytic reaction conditions were: NH3: 500 ppm, NO: 500 ppm, O2: 3%, N2 as the balance gas, total gas flow rate 100 mL / min, catalyst dosage 0.0500 g, and space velocity GHSV = 120000 mL / (h*g). cat The NO content in the exhaust gas was determined using gas chromatography-mass spectrometry (GC-MS) at a reaction temperature of 200-400℃.

[0052] Figure 2 The graph shows the denitrification efficiency of the catalysts prepared in Comparative Examples 1 and 2 at different temperatures under high mass space velocities. As can be seen from the graph, the catalytic activity of the catalyst in Comparative Example 2 is slightly lower than that in Comparative Example 1 at all test temperatures. This indicates that excessively high titanium oxysulfate loading can negatively impact denitrification performance.

[0053] Test Example 3

[0054] The denitrification performance of catalysts 1V3W-T15 and 1V3W-T0 prepared in Example 2 and Comparative Example 1 was tested in a fixed-bed reactor. The catalytic reaction conditions were: NH3: 500 ppm, NO: 500 ppm, O2: 3%, N2 as the balance gas, total gas flow rate 100 mL / min, catalyst dosage 0.1200 g, and space velocity GHSV = 50000 mL / (h*g). cat The NO content in the exhaust gas was determined using gas chromatography-mass spectrometry (GC-MS) at a reaction temperature of 150-450℃.

[0055] Figure 3The graph shows the denitrification efficiency of the catalysts prepared in Example 2 and Comparative Example 1 at different temperatures and at relatively low mass hourly space velocities. As can be seen from the graph, when the test temperature is 150–300°C, the denitrification efficiency of the catalyst in Example 2 is significantly higher than that in Comparative Example 1. Specifically, in the temperature range of 150–250°C, the denitrification efficiency of Example 2 is 8–29% higher than that of Comparative Example 1. Example 2 achieves a denitrification efficiency of 90% at a low temperature of only 225°C, which is 75°C lower than the temperature required for Comparative Example 1. The temperature range in which Example 2 achieves a high denitrification efficiency of over 95% is 250–450°C, which is 100°C wider than that of Comparative Example 1.

[0056] Test Example 4

[0057] The denitrification performance of the K2O-supported catalyst from Example 2 and the K2O-supported catalysts 1K-1V3W-T15 and 1K-1V3W-T0 prepared in Comparative Example 1 under alkali metal poisoning was tested in a fixed-bed reactor. The catalytic reaction conditions were: NH3: 500 ppm, NO: 500 ppm, O2: 3%, N2 as the balance gas, total gas flow rate 100 mL / min, catalyst dosage 0.0500 g, and space velocity GHSV = 120000 mL / (h*g). cat The NO content in the exhaust gas was determined using gas chromatography-mass spectrometry (GC-MS) at a reaction temperature of 150-400℃.

[0058] Figure 4 The figure shows the denitrification efficiency of the catalysts prepared in Example 2 and Comparative Example 1 of this invention and their K2O-loaded catalysts at high mass space velocities. As can be seen from the figure, under alkali metal poisoning conditions, the denitrification efficiency of 1K-1V3W-T15 is significantly higher than that of 1K-1V3W-T0 across the entire temperature range of 150–400℃, with an increase of 4–19%. Under high space velocities and high K2O loading, 1K-1V3W-T15 can still maintain a denitrification efficiency of over 90% at 400℃.

[0059] Figure 5 The figures show the NH3-TPD curves of the catalysts prepared in Examples 1-3 and Comparative Example 1 of this invention. As can be seen from the figures, the total acid content of the catalysts in Examples 1-3 increased by 103-139 μmol / g compared to the catalyst in Comparative Example 1, with the strong acid content increasing by 75-89 μmol / g (see Table 1 for details). The acidity of the catalysts in Examples 1-3 mainly originates from titanium oxysulfate, where the sulfate ions can serve as additional adsorption sites for NH3, promoting the NH3-SCR reaction. Furthermore, sulfate ions can preferentially consume external alkali metals, mitigating their toxic effects. This is a key reason for the improved low-temperature catalytic denitrification activity and alkali metal resistance of the catalysts of this invention.

[0060] Table 1 below shows the distribution of acidic sites for catalysts 1V3W-T10, 1V3W-T15, 1V3W-T20, and 1V3W-T0:

[0061] Figure 6 The figures show the H2-TPR curves of the catalysts prepared in Examples 1-3 and Comparative Example 1 of this invention. As can be seen from the figures, the H2 reduction peak temperature of the catalysts in Examples 1-3 is 15-19°C earlier than that of the catalyst in Comparative Example 1. This invention uses titanium oxysulfate to modify the vanadium-based catalyst, improving the reactivity of vanadium species and surface active oxygen, which is particularly beneficial for improving the redox performance of the catalyst. Therefore, the H2 reduction peak temperature is advanced, which is another important reason for the improved catalytic activity of the catalyst in the medium / low temperature range of this invention.

[0062] In summary, the vanadium-based denitration catalyst modified with titanium oxysulfate described in this invention is suitable for denitration under medium-low temperature and high-alkali metal flue gas conditions. This catalyst operates at a mass hourly space velocity (WHSV) of 120,000 mL / (h*g). cat Under these conditions, the catalytic denitrification efficiency is 11-15% higher than that of ordinary vanadium-based catalysts when operating in the low-temperature range of 150-250℃, and the denitrification efficiency can be maintained above 95% when operating in the high-temperature range of 300-400℃; at a mass hourly space velocity of 50000 mL / (h*g) cat Under the conditions of 150-300℃, the catalytic denitrification efficiency is 8-29% higher than that of ordinary vanadium-based catalysts when operating in the low-temperature range. The high-activity temperature window with a denitrification efficiency of over 95% is 100℃ wider than that of ordinary vanadium-based catalysts. Under alkali metal loading, the catalytic denitrification efficiency across the entire temperature range is 4-19% higher than that of ordinary vanadium-based catalysts, and it has strong resistance to alkali metal poisoning.

[0063] Although the present invention has been described in detail through the preferred embodiments above, it should be understood that the above description should not be considered as a limitation of the present invention. Various modifications and substitutions to the present invention will be apparent to those skilled in the art after reading the above description. Therefore, the scope of protection of the present invention should be defined by the appended claims.

Claims

1. A vanadium-based denitration catalyst modified with titanium oxysulfate, characterized in that, The vanadium-based denitration catalyst modified with titanium oxysulfate comprises: a support, and an active component and an additive supported on the support; wherein the support comprises anatase titanium dioxide containing titanium oxysulfate.

2. The vanadium-based denitration catalyst modified with titanium oxysulfate according to claim 1, characterized in that, The mass fraction of the titanium oxysulfate in the carrier is ≥5 wt% and <30 wt%, more preferably 5-25 wt%, and most preferably 10-20 wt%.

3. The vanadium-based denitration catalyst modified with titanium oxysulfate according to claim 1 or 2, characterized in that, The active component includes vanadium pentoxide, and the auxiliary component includes tungsten oxide or molybdenum oxide.

4. The vanadium-based denitration catalyst modified with titanium oxysulfate according to any one of claims 1-3, characterized in that, Based on a total mass of 100 wt% of the vanadium-based denitration catalyst modified with titanium oxysulfate, the carrier mass percentage is 88–97.5 wt%, preferably 90–96 wt%; the active component mass percentage can be 0.5–5.0 wt%, preferably 0.6–3.0 wt%; and the additive mass percentage can be 2.0–10.0 wt%, preferably 3.0–8.0 wt%.

5. A method for preparing a vanadium-based denitration catalyst modified with titanium oxysulfate according to any one of claims 1-4, characterized in that, The preparation method includes the following steps: adding a solution containing ammonium metavanadate and ammonium metatungstate / ammonium heptamolybdate to a mixed support material of titanium sulfate and titanium dioxide, mixing evenly, and then drying and calcining to obtain the titanium sulfate-modified vanadium-based denitrification catalyst.

6. The preparation method according to claim 5, characterized in that, The mass ratio of titanium sulfate to titanium dioxide is 2 to 10:

25.

7. The preparation method according to claim 5 or 6, characterized in that, The molar ratio of ammonium metavanadate to co-solvent is 1:2 to 3, preferably 1:2; the mass ratio of titanium sulfate, ammonium metavanadate, and ammonium metatungstate / ammonium heptamolybdate is 100 to 800: 9 to 90: 30 to 250.

8. The preparation method according to any one of claims 5-7, characterized in that, The calcination heating rate is 2-10℃ / min, preferably 2℃ / min; the calcination temperature is 300-650℃, preferably 300-500℃; and the calcination time is 3-6h, preferably 4h.